Sistem Ekonomi Politik Dalam Negara Islam - Shahrukh Rafi Khan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
This article explain about the contemporary works of Islamic studies, especially in connection with the issues of Islamic economy and politic. The economic and politic issues in Islamic system would be an easy to apply the process if there was a consensus among Moslem scholars. Unfortunately, it is very difficult to find the consensus, so the article just discuss the important controversies about it. After understanding well that the Islamic state theoretically is a legal entity, the writer tries to study on the structure of economy and politic in Islamic system. The benefit way and often used is comparing between the Islamic system and the socialism as the theoretical entities. This way is used in framework as written above. Following the consensus of the scholars, the successful of an Islamic state depends on its capacity increating the Islamic mechanism, especially in relation with preceptor mechanism.